2019
DOI: 10.1007/s40135-019-00220-1
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Microinvasive Glaucoma Surgery Concurrent With Cataract Extraction

Abstract: Purpose of Review In this article, we review the current options for microinvasive glaucoma surgery (MIGS) combined with cataract extraction in the USA and the efficacy of the various approaches. Recent Findings MIGS is a rapidly growing area of research and clinical interest. Available surgeries aim to reduce intraocular pressure by improving aqueous outflow through the trabecular or subconjunctival pathways or by reducing aqueous production. Summary Multiple approaches to MIGS are utilized in clinical practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
1
0
0
Order By: Relevance
“… 31 In our study, each case of inflammation was resolved with steroid therapy with proper patient compliance. This finding suggests the need for a more aggressive steroid regimen with a slower taper in the first month after ECP, aligning with the opinion set forth by Tassel et al 32 Our study confirms a potential IOP elevation effect of ECP, possibly induced by inflammation. Interestingly, with regards to the difference in the incidence of CME in the KDB group, previous studies have shown a greater incidence with ECP instead.…”
Section: Discussionsupporting
confidence: 92%
“… 31 In our study, each case of inflammation was resolved with steroid therapy with proper patient compliance. This finding suggests the need for a more aggressive steroid regimen with a slower taper in the first month after ECP, aligning with the opinion set forth by Tassel et al 32 Our study confirms a potential IOP elevation effect of ECP, possibly induced by inflammation. Interestingly, with regards to the difference in the incidence of CME in the KDB group, previous studies have shown a greater incidence with ECP instead.…”
Section: Discussionsupporting
confidence: 92%